Geogebra Learning Management Strategy in Mathematics - Sandra, Erika Dwi; Lian, Bukman; Putra, Alhadi Yan (Journal of Social Work and Science Education, 2021)
This qualitative study analysed how learning management methods with Geogebra in mathematics are implemented, the roles of instructors and students in learning management strategies with Geogebra in mathematics, and the challenges encountered in learning management strategies with Geogebra in mathematics. The results showed that Mathematics instructors at SMA Negeri Sub Rayon 03 OKU Timur in South Sumatra have begun to experiment with using technology-based learning resources in the classroom. Mathematics instructors at SMA Negeri Sub Rayon 03 OKU Timur South Sumatra have an active part in learning management practices utilizing Geogebra. Students from SMA Negeri Sub Rayon 03 OKU Timur South Sumatra played an important part in the learning management approach using Geogebra, expressing their enthusiasm for learning mathematics with Geogebra.